Can there be a burden of the best explanation?. (April 2018) - Ribeiro, Gustavo
In this article I address a foundational question in evidence law: how should judges and jurors reason with evidence? According to a widely accepted approach, legal fact-finding should involve a determination of whether each cause of action is proven to a specific probability. In most civil cases, the party carrying the burden of persuasion is said to need to persuade triers that the facts she needs to prevail are "more likely than not" true. The problem is that this approach is both a descriptively and normatively inadequate account of reasoning with evidence in law. It does not offer a plausible picture of how people in general, and legal fact-finders in particular, reason with evidence. And it turns out that if we try to do what the approach tells us, we end up with absurd results. Faced with these difficulties, a group of evidence scholars has proposed an alternative. According to them, legal fact-finding should involve a determination of which hypothesis best explains the admitted evidence, rather than whether each cause of action is proven to a specific probability. My main contributions in this article are twofold. First, I elaborate on the many descriptive, normative and explanatory considerations in support of an explanation-based approach to standards. Second, I offer novel replies to pressing objections against that same approach.